2021
DOI: 10.3390/microorganisms9010132
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Forest Malaria: A Review of More than 20 Years of Epidemiological Investigation

Abstract: In the south and southeast regions of Brazil, cases of malaria occur outside the endemic Amazon region near the Atlantic Forest in some coastal states, where Plasmodium vivax is the recognized parasite. Characteristics of cases and vectors, especially Anopheles (Kerteszia) cruzii, raise the hypothesis of a zoonosis with simians as reservoirs. The present review aims to report on investigations of the disease over a 23-year period. Two main sources have provided epidemiological data: the behavior of Anopheles v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
0
7
0
2
Order By: Relevance
“…Since no P. falciparum co-infection was disclosed, this unusual severity clinical manifestation could be related to preexisting comorbidity (diabetes) associated with the delay of the diagnosis, since the signs and symptoms of human malaria infections originating from non-human primates in the Atlantic Forest are usually mild to moderate. (34) The malaria case here reported showed the reemergence of human malaria in the southernmost Brazil as well as in South America as a whole, since countries with territories of similar or lower latitudes (Uruguay, Chile and Argentina) have been considered malaria free areas for two decades now. (35) In Rio Grande do Sul, as in other Brazilian areas of extra-Amazonia, the large-time gap with no malaria case detection certainly contribute to rule out the possibility of malaria infection in febrile patients.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Since no P. falciparum co-infection was disclosed, this unusual severity clinical manifestation could be related to preexisting comorbidity (diabetes) associated with the delay of the diagnosis, since the signs and symptoms of human malaria infections originating from non-human primates in the Atlantic Forest are usually mild to moderate. (34) The malaria case here reported showed the reemergence of human malaria in the southernmost Brazil as well as in South America as a whole, since countries with territories of similar or lower latitudes (Uruguay, Chile and Argentina) have been considered malaria free areas for two decades now. (35) In Rio Grande do Sul, as in other Brazilian areas of extra-Amazonia, the large-time gap with no malaria case detection certainly contribute to rule out the possibility of malaria infection in febrile patients.…”
mentioning
confidence: 71%
“…Since no P. falciparum co-infection was disclosed, this unusual severity clinical manifestation could be related to pre-existing comorbidity (diabetes) associated with the delay of the diagnosis, since the signs and symptoms of human malaria infections originating from non-human primates in the Atlantic Forest are usually mild to moderate. 34 …”
mentioning
confidence: 99%
“…Antibodies against PvMSP1 19 were identified in more than half of our sample set, followed by those for PfMSP1 19 , and in smaller percentages by those against the different recombinant proteins of P. malariae (PmMSP1 F1 , PmMSP1 F2 , PmMSP1 F3 , PmMSP1 F4 and PmMSP1 19 ), corroborating with the data obtained in Brazilian historical data of malaria that have demonstrated the predominance of P. vivax over P. falciparum over the years [ 35 , 36 ]. However, comparing the recognition of the recombinant proteins using the RI obtained for each protein, very similar levels were obtained for PvMSP1 19 and P. malariae , mainly for PmMSP1 F1 and PmMSP1 F3 in the Atlantic Forest region, a documented area for the presence of P. malariae infections [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study carried out on humans living on the border of the Atlantic tropical rainforest region of Rio de Janeiro identified P. falciparum in humans with malaria [ 45 ]. Recent evidence points to the presence of P. falciparum in a silent cycle, detected only by molecular methods in asymptomatic individuals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the 18S rRNA and circumsporozoite genes of Plasmodium species, one study reported natural human infections with P. brasilianum ( Pbra ), an Alouatta monkeys’ parasite, in individuals from the Venezuelan Amazon, South America [ 59 ]. Likewise, Pbra was also reported to cause human infection in some coastal areas in Brazil [ 60 ]. In Malaysia, Pin , Pin -like, Pct , and P. simiovale parasites were found to infect humans based on analysis of the 18S rRNA and COXI genes [ 58 , 61 ].…”
Section: Role Of Other Zoonotic Species In Human Malaria: P...mentioning
confidence: 99%